Upaya Pengendalian Hiperurisemia melalui Skrining dan Edukasi pada Populasi Dewasa di Gereja Asisi Jakarta - Tambunan, Nicholas Albert; Santoso, Alexander Halim; Gunaidi, Farell Christian; Johan, Richver Framanto; Haryanto, Ines (Jurnal Pengabdian Bidang Kesehatan, 2025)
Hyperuricemia is a medical condition characterized by an increase in uric acid levels in the blood above normal limits, which can trigger various metabolic complications such as gouty arthritis, urate nephropathy, and cardiovascular disease. In the early stages, hyperuricemia is often asymptomatic, therefore routine investigation of uric acid level are an important step in early detection. The Community Service Program (PKM) implemented at the Asisi Church, Tebet District, aims to increase public awareness of the importance of early detection of hyperuricemia through blood uric acid level screening activities. This activity uses the Plan-Do-Check-Act (PDCA) approach, which includes capillary blood tests with Point-of-Care Testing (POCT) tools and education on risk factors, symptoms, and prevention of hyperuricemia. Of the 68 participants, all participants showed uric acid levels within the normal range. These results emphasize the importance of education and routine screening efforts to maintain uric acid levels within normal limits, prevent complications in the future, and build public awareness of the importance of a healthy lifestyle to maintain quality of life sustainably.